Coupled bending-torsional vibration analysis for rotor-bearing system with rub-impact of hydraulic generating set under both dynamic and static eccentric electromagnetic excitation. (June 2021) - Zhang, Jinjian; Zhang, Leike; Ma, Zhenyue; Wang, Xueni; Wu, Qianqian; Fan, Zhe
Abstract: Modern industrial requirements are continuously demanding better performance, smaller clearance, higher rotational speed and higher load from hydraulic generating set, under this circumstance, vibration mitigation is of considerable importance for safe and efficient functioning of rotor-bearing system. The overall goal of this research is to reveal the mechanism for unexpected nonlinear vibration induced by combined action of machine and charge load from hydraulic generating set. At first, a coupled bending-torsional rotor-bearing system with rub-impact under electromagnetic excitation for hydraulic generating set is established, meanwhile, a general model of unbalanced magnetic pull, considering both dynamic and static eccentricities between stator and rotor, is introduced to the system, and corresponding equations of motion are obtained according to Lagrange equation. Secondly, the effects from excitation current, mass eccentricity, radial stiffness of stator, dynamic and static eccentricities on vibration response of system are investigated thoroughly, by means of numerical method. And nonlinear dynamic behavior of system is illustrated through bifurcation diagrams, Poincaré maps, trajectories, time domains and frequency spectrums. Finally, comparisons that with and without mixed eccentricities is conducted in term of nonlinear performance, disclosing that dynamic characteristic of system changes dramatically when composited eccentricities are taken into account. The analysis contributes to a deep understanding of complex nonlinear dynamic phenomena with benefit for forecasting and diagnosing system vibration due to electromechanical excitation in hydraulic generating rotor system.